Vapor-Liquid-Liquid Equilibrium of Methanol, Cyclohexane, and Hexane Systems at 0.1 MPa: Binary and Ternary Phase Behavior Analysis - Q.F. Gillani; P. Askar; A. Ospanova; M.A. Jamali; N. Nuraje (Eurasian Chemico-Technological Journal)
This study presents an evaluation of the liquid-liquid equilibria (LLE) for both binary and ternary systems involving methanol, cyclohexane, and n-hexane at a pressure of 1 MPa. The investigation encompasses a comprehensive analysis of phase behavior, including thermodynamic modeling, and graphical representations. The binary system of methanol and cyclohexane is examined extensively to understand their phase equilibrium at varying temperatures, with a focus on the T-xx diagram, activity coefficient calculations, and vapor-liquid equilibrium (VLE) analyses. Furthermore, the ternary system incorporating n-hexane alongside methanol and cyclohexane is investigated to explore the intricacies of multicomponent phase behavior. Through the utilization of thermodynamic models such as the Non-Random Two-Liquid (NRTL) model and Universal Quasi-Chemical (UNIQUAC) model, key insights into the phase compositions, distribution coefficients, azeotropes, and residue curves are elucidated. The findings from this study provide valuable insights into the thermodynamic interactions within these systems, offering essential guidance for process design and optimization in various industrial applications.